The Hanford plaintiffs : voices from the fight for atomic justice - Pritikin, Trisha T. (University Press of Kansas, 2020)
"For four decades, from its opening as a Manhattan Project outpost during World War, the Hanford nuclear facility in Washington State regularly released radiation into the air and water surrounding it, blanketing farms, towns, and the Columbia River. Residents - many of them families of Hanford workers - were repeatedly assured that facility posed no threat, despite rising rates of illness and death in both people and animals. Not until the 1980s, when documents related to nuclear testing were finally declassified, did the public learn that the government had known all along that Hanford was a danger to the people of the Pacific Northwest. Starting in 1991, thousands of downwinders filed personal injury claims against the contractors who operated Hanford, seeking recompense for their high rates of cancer, thyroid disease, and other issues. In The Hanford Plaintiffs, Trisha Pritikin - a Hanford downwinder, attorney, and named plaintiff - tells the story of Hanford, its downwinders, and their battle for justice. She gives historical context to both Hanford and the larger issue of American nuclear testing, drawing especially on the experiences of Nevada Test Site downwinders. She details In Re Hanford, the class action suit, and the multitude of uphill battles downwinders face in a legal system that protects the government on all fronts. But the core of the book, its greatest contribution, is the set of 24 oral histories from Hanford plaintiffs. Here is the personal cost of America's nuclear power, told in the words of those who struggled not just with illness and loss but also to be believed in the face of government insistence that nothing was wrong"--